Love Through Patience: A Contribution to the Kierkegaardian Discussion on the Spiritual Nature of Love Relationships - Raquel Carpintero (Religions)
This paper seeks to make a modest contribution to the ongoing Kierkegaardian discussion concerning the spiritual nature of love relationships, particularly those involving romantic elements. It introduces patience as a key element in understanding the love of the spirit, diverging from perspectives commonly found in recent Anglophone Kierkegaardian literature. Since, in Kierkegaard’s works, the spirit is conceived as an intermediary being positioned between time and eternity, I argue that the spirit’s love must be approached through patience, which is the concrete space where time and eternity intertwine. The argument unfolds in three steps: first, I present Kierkegaard’s understanding of human love as a work, highlighting the significance of the neighbor, which refers to the mode of loving rather than the object of love; second, I outline the challenges inherent in Kierkegaard’s conception of love and propose an approach that emphasizes the dialectic between transcendence and immanence; third, I argue that patience is the concrete means by which this dialectic unfolds within the individual’s existence.